Differential measurement of small and large bowel transit times in constipation and diarrhoea: A new approach. Issue 5 (May 1975) - Waller, S L
Abstract : Differential measurements of small and large bowel transit times were performed in 13 subjects iwth a radiotelemetering pressure-sensitive capsule incorporating less than 10mugCi of 51-Cr. Six patients had constipation. The other seven patients had diarrhoea due to the irritable bowel syndrome (3), following vagotomy and pyloroplasty (3), or due to laxative abuse (1). This new method enables the gastric, small intestinal, and colonic transit times to be measured differentially in the same subject. The capsule can be localized in the gut lumen by reference to the characteristic pressure pattern and in relation to bony landmarks by the radioactive marker as frequently as desired without recourse to radiographs. The results show that gastric emptying and small intestinal transit did not differ in constipation and diarrhoea. By contrast the mean colonic transit was significantly faster (P smaller than 0.01) in diarrhoea whatever the cause (17.5 plus or minus 4.1 hours) than in constipation (118 plus or minus 4.1 hours).